Water Quality Assessment at Consumption Points in High School Campuses in the Province of Antique, Philippines - Yazawa, Taishi; Geroy Rubite, Kenn Joshua; Macabata-Rubite, Princess Eden (Pusbindiklatren Bappenas, 2025)
This research presents a comprehensive citizen-scientific water quality assessment and evaluation, focusing on water quality at the points of water consumption in public and private high school campuses in the Province of Antique, Philippines. The water quality assessment showed that Escherichia coli was detected in several samples from tap water exclusively used for handwashing by public school students, indicating potential contamination sources such as outdated treatment facilities. To improve the WASH environment of the provincial school campuses, old facilities, such as filters and pipes, need to be checked and renovated to avoid contamination caused by penetration and leakage. School-level and individual practices, such as chlorination, covering water tanks, and encouragement of handwashing, could be the first step. The citizen scientific methodology facilitated the collection of water quality information and enhanced discussions with stakeholders, generating practical and affordable solutions based on the findings.